Social context matters: characterizing adolescent cooperation strategies when perceiving the other as a peer versus computer partner - Liu, Wenda; Mark, Isabella; Korn, Christoph W.; Rosenblau, Gabriela (Journal of adolescence, 2025)
Introduction Cooperation is a crucial prosocial skill refined during adolescence, a period marked by increased interactions with peers and artificial intelligence agents. While adolescents prioritize peer relationships, it remains unclear whether this translates into increased trust and reciprocity during social exchange. This study explores whether adolescents differentiate their cooperation strategies when interacting with human peers versus adaptive or fixed computer partners. Methods Adolescents (N = 67, 36 female, mean age: 12.3 ± 3.0 years) were recruited and invited into the laboratory to play a multiround trust game, first with a peer. In subsequent games, they were told that they continued to play with a peer (i.e., social condition) but they were playing with an adaptive algorithm. In the remaining games, they were correctly informed that they were playing with a computer (i.e., nonsocial condition). Results Adolescents sustained cooperation more when interacting with adaptive versus fixed computer partners. In the social condition, older adolescents and those with higher IQs and social skills were more prosocial than in the non-social condition. We fitted direct reciprocity strategies, reinforcement learning (RL) models, and a combination thereof to participants' choices. Direct reciprocity best captured adolescents' cooperation behavior. In the social condition, however, adolescents reinitiated cooperation more often after previously defecting. The winning model in the social condition was a more generous direct reciprocity strategy than the standard model. It used an RL forgiveness term that prescribed an evolving tendency to reinitiate cooperation. Conclusion Overall, we show that both partner adaptivity and social context play an important role in adolescents' cooperation decisions.
Gesehen am 30.11.2025